Discovery of new chiral sulfonamides bearing benzoxadiazole as HIF inhibitors for non-small cell lung cancer therapy: design, microwave-assisted synthesis, binding affinity, in vitro antitumoral activities and in silico studies. (20th January 2022) - Kahraman, Demet Taşdemir; Karaküçük-İyidoğan, Ayşegül; Saygideger, Yasemin; Oruç-Emre, Emine Elçin; Taskin-Tok, Tugba; Başaran, Eyüp; İlhan, Sedat; Demir, Burcu Saygıdeğer; Üren, Aykut; Bayram, Hasan
Abstract : Thirty-four chiral compounds having benzoxadiazole and sulfonamide moieties on the skeleton have been synthesized. The  in vitro  cytotoxic activity and apoptotic effects of these compounds have been evaluated using the A549 lung cancer cell line. Abstract : Hypoxia-inducible factors (HIF) are among the targeted treatment strategies with increasing promise in lung cancer, and are known to play a role in tumour growth and other oncogenic properties in cancer cells. Therefore, there is an urgent need for selective HIF inhibitors that can provide therapeutic benefits against lung cancer. In this study, thirty-four chiral compounds designed by combining benzoxadiazole and sulfonamide moieties on the skeleton of the same molecule have been synthesized in S and R enantiomeric forms. In vitro cytotoxic activity and apoptotic effects of the compounds (1a–17a, 1b–17b ) have been evaluated using A549 lung cancer cell line and the compounds that induced apoptosis in A549 cells and reduced mRNA expression levels of HIF-targeted genes have been evaluated. Consequently, four molecules with high potential have been developed as target compounds (4b, 6a, 6b and 7a ), and the pharmacokinetic properties of these molecules have been determined theoretically. Also, emerging computational methods such as molecular docking, which are conducted to estimate the modes of the interactions of the compounds with HIF-1β, calculations of binding energy and ADMET analysis, have been applied to support the results of in vitro cytotoxic activity. Taken together with all the results, compound 6a with the R configuration seems to be a promising HIF-1β inhibitor candidate for targeted therapy.